An Investigation on the Effects of Oil Price, Industrial Production and Agricultural Production on Inflation in Kazakhstan Using the Toda-Yamamoto Model with Structural Breaks - Talimova, Lyazat; Sembekov, Amir Kateyevich; Kuchukova, Nurilya; Assilova, Aizhan Sarsenovna; Omarova, Gulnara; Tlesova, Aigul; Myrzabekkyzy, Kundyz (International Journal of Energy Economics and Policy, 2025)
This article analyzes the impact of oil prices, as well as industrial and agricultural production activities, on inflation in the Kazakh economy using a structural break model. The research was conducted using annual data from 1996 to 2023, employing Toda-Yamamoto causality and Gregory-Hansen cointegration tests. The aim of the study is to provide strategic recommendations to policymakers by examining the dynamic relationships between various economic indicators. The macroeconomic data were analyzed to understand how industrial and agricultural production, alongside oil prices, influence inflation. The findings reveal that oil prices have a direct and statistically significant impact on inflation. Additionally, a bidirectional causality relationship was identified between industrial production and inflation. In contrast, agricultural production was found to affect inflation in the short term but does not have a significant long-term influence. This suggests that agricultural production plays a limited role in the dynamics of inflation. Based on the analysis, the study emphasizes the need to prioritize these factors in economic policy, particularly the impacts of oil prices and industrial production on inflation. It also highlights the importance of increasing industrial production capacity and wisely utilizing oil revenues to support economic diversification. These findings offer valuable guidance for ensuring Kazakhstan’s economic stability and fostering long-term growth.